1999
DOI: 10.1093/oxfordjournals.molbev.a026084
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic evidence for horizontal transmission of Wolbachia in host- parasitoid associations

Abstract: Endosymbiotic Wolbachia infect a number of arthropod species in which they can affect the reproductive system. While maternally transmitted, unlike mitochondria their molecular phylogeny does not parallel that of their hosts. This strongly suggests horizontal transmission among species, the mechanisms of which remain unknown. Such transfers require intimate between-species relationships, and thus host-parasite associations are outstandingly appropriate for study. Here, we demonstrate that hymenopteran parasito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
395
3
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 384 publications
(416 citation statements)
references
References 27 publications
15
395
3
3
Order By: Relevance
“…Consistent with a previous study (Vavre et al 1999a), all individuals were coinfected by the three Wolbachia strains wAtab1, wAtab2, and wAtab3. Nine of the 46 triply infected females (19.1%) produced no progeny, whereas all of the remaining 37 females were fertile and produced an average (Ϯ SD) of 106.2 (Ϯ 20.0) offspring.…”
Section: Infection Status and Sterility Of Untreated Femalessupporting
confidence: 87%
See 2 more Smart Citations
“…Consistent with a previous study (Vavre et al 1999a), all individuals were coinfected by the three Wolbachia strains wAtab1, wAtab2, and wAtab3. Nine of the 46 triply infected females (19.1%) produced no progeny, whereas all of the remaining 37 females were fertile and produced an average (Ϯ SD) of 106.2 (Ϯ 20.0) offspring.…”
Section: Infection Status and Sterility Of Untreated Femalessupporting
confidence: 87%
“…Specific polymerase chain reaction (PCR) assays were used to detect the three Wolbachia strains previously described in A. tabida (Vavre et al 1999a). Based on the Wolbachia wsp gene sequences of the three strains (Genbank accession number AF124856, AF124857, AF124859), specific primers were designed for each of them: 5Ј-TGG TAT TAC AAA TGT AGC-3Ј for wAtab1, 5Ј-ACC TAT AAG AAA GAC AAG-3Ј for wAtab2 (172F in Zhou et al 1998), and 5Ј-AAA GGG GAC TGA TGA TGT-3Ј for wAtab3.…”
Section: Diagnostic Polymerase Chain Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequences generated in this study are indicated in bold. The bar represents a distance of 0.050 (about 25 MY if a wsp evolutionary rate of 0.2% per MY is assumed, Wenseleers et al, 2001). and Solignac, 1995;Wenseleers et al, 1998;Werren et al, 1995a, b;Werren and Windsor, 2000) or more rarely, triple infections (Kondo et al, 2002;Vavre et al, 1999). A stable triple Wolbachia infection has also been created artificially by microinjection of an additional strain in double infected Drosophila (Rousset et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Facultative associations are prone to turnover, and this may channel interspecific exchange. For Wolbachia specifically, incongruent cophylogenies with hosts (Shoemaker et al., 2002; Vavre, Fleury, Lepetit, Fouillet, & Bouletreau, 1999), the observation that phylogenetically diverse taxa share identical or similar Wolbachia strains (Huigens, de Almeida, Boons, Luck, & Stouthamer, 2004; Noda et al., 2001) and recombination between strains (Bordenstein, Wernegreen, & Werren, 2006; Werren & Bartos, 2001) indicate that interspecific transmissions of Wolbachia are common on an evolutionary time scale (Ahmed, Breinholt, & Kawahara, 2016; Baldo et al., 2008; O'Neill, Giordano, Colbert, Karr, & Robertson, 1992; Russell, Latorre, Sabater‐Muñoz, Moya, & Moran, 2003). Yet the number of studies documenting interspecific transmission or spread of strains in natural populations remains few (e.g., Hoshizaki & Shimada, 1995; Kriesner, Hoffmann, Lee, Turelli, & Weeks, 2013; Schuler et al., 2013; Turelli & Hoffmann, 1991).…”
Section: Introductionmentioning
confidence: 99%